2017
DOI: 10.3357/amhp.4552.2017
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Physiological Training at NASA

Abstract: CO2 exposure training is an important tool to educate astronauts about their potential acute CO2 symptoms. Wide interindividual and temporal variations were observed in symptoms reported during astronaut CO2 exposure training. Headache could not be relied on as a marker of acute exposure during testing since fewer than half the subjects reported it. Our results support periodic refresher training since symptoms may change over time. Further study is needed to determine the optimal interval of training to maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
7
0
4
Order By: Relevance
“…Therefore, neither device can simulate high-altitude training. The level of inhaled CO 2 in own research was lower compared with other research, in which gas mixtures containing >2% CO 2 in the inhaled air were used [ 6 , 32 ]. Thus, it would seem that inhaling air containing an average of 0.19% CO 2 would not lead to significant changes in work efficiency, acid–base balance, or current physiological responses of the body.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, neither device can simulate high-altitude training. The level of inhaled CO 2 in own research was lower compared with other research, in which gas mixtures containing >2% CO 2 in the inhaled air were used [ 6 , 32 ]. Thus, it would seem that inhaling air containing an average of 0.19% CO 2 would not lead to significant changes in work efficiency, acid–base balance, or current physiological responses of the body.…”
Section: Discussionmentioning
confidence: 57%
“…The study concluded that there was a significant reduction in PaO2 from baseline and an increase in other respiratory adverse effects [16]. Another study conducted in a cohort of 130 astronauts subjected to high CO2 pressures during controlled training showed a significantly higher incidence of headache in the exposed group, in addition to respiratory symptoms and difficulty in concentrating [17]. At the University of Wollongong (Australia), a study on the effects of CO2 inhalation on workers wearing respiratory protection devices showed that high levels of carbon dioxide were associated with feelings of discomfort and significantly reduced tolerance and time of device use [18].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of hypercapnia include lightheadedness, dizziness, and headaches, and can ultimately lead to collapse and death. 8,9 Mask protection classes comprise simple mouth-nose-protection (MNP) devices as well as filtering face piece (FFP) 1, 2 and 3 masks. FFP masks with and without expiration valves are currently in frequent use around the globe.…”
Section: Introductionmentioning
confidence: 99%